Study of Characteristic MPX5700AP Sensor For Pressure System Monitoring Based Various Units - Abdul Hadi; Zainal Abidin; Tri Dewantoro (International ABEC, 2022)
Implementation of MPX5700AP sensor is very much among practitioners and academics to measure pressure. However, the sensor accuracy obtained is always far from the measurement due to reading errors. This study calculates the accuracy of the MPX5700AP sensor in reading measurements. The reading of this pressure measurement is measured by a standard measurement of environmental pressure, which is atmosphere pressure. From the research obtained, the MPX5700AP sensor has a voltage output with an accuracy of 98.81%. The reading accuracy for each measurement conversion is 96.08%, 95.95%, and 95.94% between kPa, Psi, and mmHg respectively.